Pearl and Wagner : one funny day - McMullan, Kate.; Alley, R. W., (Robert W.) (New York : Dial Books for Young Readers, 2009)
April Fools' Day turns into a bad day for Wagner the mouse when his best friend, Pearl the rabbit, and other children and adults at school play tricks on him.
"Level 2"--Cover p. [4].
Booklist.
School Library Journal starred.
Wilson's Children.
Booklist, November 2008.
Bulletin (Center for Children's books), June 2009.
Keywords: Animals -- Juvenile fiction; April Fools' Day -- Juvenile fiction; Mice -- Juvenile fiction; Practical jokes -- Juvenile fiction; Rabbits -- Juvenile fiction; Schools -- Juvenile fiction; Animals -- Fiction; April Fools' Day -- Fiction; Mice -- Fiction; Practical jokes -- Fiction; Rabbits -- Fiction; Schools -- Fiction; Animals -- Fiction; April Fools' Day -- Fiction; Mice -- Fiction; Practical jokes -- Fiction; Rabbits -- Fiction; School stories